Transition Planes for Visual Comfort: Out View with Complex Fenestration System Design at Restaurants in Spain - Urtza Uriarte; Jose Miguel Rico-Martinez; Joan L. Zamora; Rufino J. Hernández (Energies, 2021)
This work deals with daylighting for quality indoor atmospheres, considering building skins. In recent years, almost all retrofit facades of restaurants are highly glazed façades, boosting glare, sun ray absorption and overheating inside. Most of the time, they are not integrated with daylight control; therefore, lighting and out view requirements are not so balanced. Taking into account this daylighting complexity, an alternative façade system is proposed to simulate by Radiance. Previously, perception simulations are compared with measured data, in order to discretize the simulations. In addition, for one point three different view are assessed as: work plane, relation plane and the out plane. Subsequently, two virtual façade models, windows combined by complex fenestration system (CFS) as prismatic film (PF) and highly glazed façade, are tested according to daylighting. For that, three indexes have been used: daylight glare probability (DGP), daylight glare index (DGI) and daylight autonomy (DA). The results show that the proposed complex façade has a good light contribution with less absorption, while maintaining the outside view. In addition, the DGI is needed to test the out plane, because DGP is more suitable for lower luminance; therefore, each visual plane should be assessed regarding different visual comfort conditions, or parameters and methods. Accordingly, the mean DGI result of window combined by CFS is approximately lower in 5% than highly glazed façade. However, the DA of highly glazed is higher in 5%, but the DA of window combined by CFS is enough, above 80%. Definitely, the complex scene at restaurant with the proposed integrated façade system improves light performance and indoor atmosphere.